Manajemen Surveilans Epidemiologi Penyakit Potensi Kejadian Luar Biasa (KLB)Di Dinas Kesehatan Kabupaten Karanganyar Tahun 2014 - Hastuti, Nunik Maya; , Sri Sugiarsi, SKM, M.Kes; , Arief Kurniawan, SKM (2014)
Epidemiological surveillance is an activity analysis systematically and continuously against the diseases and conditions that affect the increase and spread of diseases or health problems. The accuracy and completeness of epidemiologic surveillance report delivery is an important factor related to the accuracy of the data. The purpose of this study was to determine the process of recording data, data processing, reporting and feed back reporting of epidemiological surveillance of disease outbreaks in DKK Karanganyar potential. This research is qualitative. The study population was a village midwife, health centers Surveillance Officer, Surveillance Officer and Head of Karanganyar DKK DKK P2PL Karanganyar. The results showed the recording and reporting of potential disease outbreaks epidemiological surveillance carried out every day, every week and every month reported by the village midwife Surveillance Officer Health Center reported to DKK Karanganyar then subsequently reported to the Provincial Health Office. Data processing carried out by a surveillance officer DKK Karanganyar. Feed back reporting to follow up depending on size of the problem, widespread problem, the number of cases, and the type of case. The conclusions of this study is the implementation of epidemiological surveillance management of potential disease outbreaks in DKK Karanganyar still experiencing delays in the collection of surveillance data.